The leadership thing – a unique perspective. Issue 2 (25th February 2020) - Mazze, Edward; Davis, Stanley
Abstract : Purpose: The purpose of this paper is to surface the misdirection of certain accepted organization development and executive compensation practices. Design/methodology/approach: Against a backdrop of academic leadership studies, this paper engages the authors' hands-on expertise drawn from their joint 100 plus years of organization building experience. Findings: The pragmatic consideration of leaders' performance and potential boils down to assessing their attitude, skills, knowledge and impact. Originality/value: This paper exposes the inadvertent effect of some common customs and policies on organizations.